EDUCATION OF YOUNG PEOPLE IN THE SPIRIT OF PHYSICAL ENDURANCE TO MILITARY SERVICE (Scientific journal of the Fergana State University, 2023)
this article will give tips for improving upbringing methodologies in the spirit of physical education and endurance. In this article, an observer of the importance of focusing on the physical education of our youth, educating them in the spirit of physical endurance to military service. At the same time, the article presents young people's activities that affect their physical condition and personal characteristics, health and ability to improve. Such types of upbringing are very important for the life of young people, since they need to increase their health and ability to think independently.